Flow Experience in Extensive Reading: Indonesian EFL Students’ Perceptions and Enabling Conditions - Fenty L. Siregar; Henni (Universitas Hamzanwadi, 2025)
Flow experience (FE) refers to an optimal psychological state characterized by deep involvement, enjoyment, and a sense of control during an activity. Although extensive reading (ER) is widely recognized for supporting language development, less is known about the psychological conditions that sustain learners’ engagement in ER, particularly in Indonesian EFL contexts. This study investigated Indonesian EFL students’ perceptions of FE during a two-semester ER program and examined the internal and external conditions that enabled or hindered flow. Thirty-six undergraduate English Literature students at a private university in West Java participated in the study while completing ER using the XReading platform across two consecutive semesters. A mixed-methods design was employed. Quantitative data were collected at the end of each semester using a 36-item Flow State Scale covering nine dimensions of flow. Qualitative data were then gathered through semi-structured interviews with six purposively selected students representing diverse ER achievement patterns, complemented by document analysis of XReading logs and ER-related written tasks. Results indicated that students generally experienced high levels of flow in both semesters, with higher overall flow reported in the second semester. The largest increase was observed in skill–challenge balance, suggesting that sustained ER participation strengthened learners’ ability to select texts that matched their developing proficiency. Across both semesters, book content emerged as the most influential external condition, while mood and concentration were the most salient internal conditions. Interview findings further highlighted learner autonomy in selecting texts and managing reading routines as central to students’ sense of control and immersion, although competing academic and personal demands could disrupt flow. The findings suggest that two-semester ER programs can foster sustained flow when learners have access to engaging, level-appropriate texts and meaningful autonomy, supported by teacher guidance to help students regulate attention and affect.